OVERVIEW OF THE IMPACT OF SUBSTANCE USE DISORDER ON TRAFFIC CRASHES: A CASE OF BOTSWANA - Adewumi OLADELE (Journal of Construction Project Management and Innovation)
Addictions to drug and alcohol, which stem from substance abuse (SA), are universal public health problems and cause a significant burden to individuals and societies resulting in a multitude of physical, social, economic and legal problems including transport crashes. In spite of epidemic levels of substance abuse in society, many individuals do not receive treatment at all let alone adequate treatment. This continues to make substance use disorder a major cause of transport crashes (with the attendant menace) in developing countries. Research suggests that counsellors (and other helping professionals) are disinterested in SA counselling, and have SA training, attitude, and skill deficits. There is a dearth of empirical research particularly in developing countries that addresses counsellors’ (or trainee counsellors’) knowledge and attitudes in relation to substance use and substance users. This paper therefore reviewed the effect of substance abuse, the overall burden of which could have been reduced, had there been adequate and appropriate exposure to treatment, on highway traffic crashes.